Pengaruh Economic Value Added Dan Profitabilitas Terhadap Return Saham Pada Perusahaan LQ-45 Tahun 2018-2022 - Ridwan, Muhammad; Hidajat, Sjarief (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This study aims to examine the effect of Economic Value Added and Profitability on Stock Returns in LQ-45 Companies in the Indonesia Stock Exchange from 2018 to 2022. This research is of a descriptive type with an associative quantitative approach. The research sample was selected using a purposive sampling technique from a total population of 73 companies, resulting in 23 companies being obtained. The results of this study indicate that Economic Value Added is able to provide a positive effect on Stock Returns, and Profitability is able to provide a positive effect on Stock Returns.